O efeito da musicoterapia na qualidade de vida e nos sintomas depressivos do paciente em hemodiálise - Hagemann, Paula de Marchi Scarpin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to evaluate the quality of life and depressive symptoms in hemodialysis patients before and after the process of music therapy. The specific objectives were: identify possible relationship among the sociodemographic, clinical, laboratory, quality of life symptoms of depression assessed and evaluate the systolic and diastolic blood pressure of participating patientes, before and after the music therapy process. Method: This is a prospective study of music therapeutic intervention, with evaluation before and after intervention. The study included 23 patients who underwent hemodialysis in Centro de Terapia Renal Substitutiva/Diálise do Hospital Estadual de Bauru. The patients were evaluated in two distinct phases - pre and post music therapeutic process. In the first phase all participants completed the Beck Depression Inventory (BDI-II) to evaluate symptoms of depression, and the Kidney Disease Quality of Life Short Form (KDQOL-SF) to assess quality of life. After the evaluations, participants went through individual interviews during hemodialysis session, in which sociodemographic data were collected. There were collected also, from medical records, laboratory data and data on the blood pressure of 10 hemodialysis sessions (measurements at the beginning and end of each session) prior to performing the process. After the initial assessments, music therapy sessions began, with four participants per group, eight sessions each, twice a week, for approximately seventy-five minutes. At the end of the intervention, the patients were reassessed and laboratory data and assessment of blood pressure of 10 sessions that followed the intervention were collected again. Results: There were 56.8% female, mean age of 54.9 years, means 7.1 years of schooling and mean treatment period of 31.4 months. According to the BDI-II, 60.8% of participants had symptoms of depression at baseline. After intervention of music therapy, this number...

O presente estudo teve como objetivo geral avaliar a qualidade de vida e sintomas depressivos em pacientes em hemodiálise, antes e após processo de musicoterapia. Os objetivos específicos foram: Identificar possíveis relações de influência entre os dados sociodemográficos, clínicos, laboratoriais, qualidade de vida e sintomas de depressão avaliados; e avaliar a pressão arterial sistólica e diastólica dos pacientes participantes, antes e após o processo de musicoterapia. Método: Trata-se de um estudo prospectivo, de intervenção. Participaram do estudo 23 pacientes que realizavam hemodiálise do Centro de Terapia Renal Substitutiva/Diálise do Hospital Estadual de Bauru. Os pacientes foram avaliados em duas fases distintas - pré e pós processo musicoterapêutico. Na primeira fase todos os participantes responderam ao Inventário de Depressão de Beck (BDI-II) para avaliar sintomas de depressão, e ao Kidney Disease Quality of Life Short Form (KDQOL-SF) para avaliar qualidade de vida. Após as avaliações os participantes passaram por entrevista individual durante sessão de demodiálise, na qual foram levantados dados sociodemográficos. Também foram coletados dos prontuários, dados de exames laboratoriais e dados referentes à pressão arterial de 10 sessões de hemodiálise (aferições do início e do final de cada sessão) que antecederam a realização da intervenção. Após as avaliações iniciais, tiveram início as sessões de musicoterapia, que se deram através de atendimentos com quatro participantes por grupo, sendo oito sessões com cada, duas vezes por semana, com duração média de setenta e cinco minutos. Ao final da intervenção, os pacientes foram reavaliados e forma coletados novamente dados laboratoriais e aferições de pressão arterial de 10 sessões que sucederam a intervenção. Resultados: Eram do sexo feminino 56,5%, com idade média de 54,9 anos, média de 7,1 anos de estudo e tempo médio de...
The effect of the music therapy on quality of life and depressive symptoms in patients in hemodialysis
Keywords: Musicoterapia; Hemodialise; Qualidade de vida; Depressão mental; Pressão arterial; Music therapy